Binary Vote Assignment on Cloud Quorum Algorithm for Fragmented MyGRANTS Database Replication - Noraziah, Ahmad; Ainul Azila, Che Fauzi; Herawan, Tutut; Zailani, Abdullah (Landesmuseum Krnten, 2015)
Distributed database replication is a very promising and challenging process that involves multi independent database servers in distributed environment. Data replication is one of the mechanisms to manage data since it improves data accessibility and reliability. Therefore, the storage, availability, and consistency are important issues to be addressed in order to allow distributed users efficiently and safely access data from many different sites. This paper proposed a new algorithm namely Binary Vote Assignment on Cloud Quorum (BVACQ) in order to handle fragmented database replication in distributed environment. BVACQ algorithm is capable of partitioning the database into disjoint fragments. Fragmentation in distributed database is very useful in terms of usage, reliability and efficiency. Handling fragmented database replication becomes challenging issue to administrator since the distributed database is scattered into split replica partitions or fragments. We address how to build reliable systems by using the proposed BVACQ algorithm for distributed database fragmentation by using Malaysian Greater Research Network (MyGRANTS) data in our case study. The result shows that managing fragmented database replication through proposed BVAGQ algorithm able to preserve MyGRANTS data consistency.